Procedure in nasal allergen challenge - Samoliński, Bolesław; Krzych-Fałta, Edyta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
The tests should be performed in the same room and, as far as possible, under the following, stable conditions: temperature: 20-22°C, relative humidity: 35-45%, without the presence of irritants or allergically active substances in the air. After 20-30 min of adapting the patient, the condition of the nasal mucous membrane is to be evaluated using an objective technique, rhinoscopy, and the patient’s self-evaluation. This is followed by another evaluation, in the 15th min after administration of a control solution, of the degree of nasal mucous membrane reactivity to the solution administered, using the above techniques. Two-sided application of an allergen on the surface of the nasal mucous membrane is followed by an evaluation of relative reactivity in the 15th min after administration of the allergen, using an objective technique, rhinoscopy, and the patient’s self-evaluation (Visual Analogue Scale or VAS, a score scale).